Exploiting phKL-mediated homoeologous recombinants to map stripe rust resistance gene YrAev from Aegilops variabilis - Ming Hao; Yazhou Li; Chaolan Fan; Hong Chen; Yongxin Nie; Fang Wang; Jiangtao Luo; Bo Jiang; Xue Chen; Xuejiao Chen; Zhongwei Yuan; Shunzong Ning; et al. (Crop Journal)
Aegilops variabilis (SvSvUvUv) is a source of resistance to wheat stripe rust. The phKL locus in Chinese common wheat landrace Kaixian-Luohanmai (KL) can induce homoeologous wheat-alien chromosome pairing and recombination. In this study, we confirmed that the whole 2Sv chromosome introgressed into wheat from Ae. variabilis accession AS116 conferred all-stage stripe rust resistance. The underlying gene(s), named YrAev, was mapped to the long arm 2SvL using an F2 population. Two 2Sv-2B recombinants, derived from a cross of the 2Sv (2B) chromosome substitution line and KL, were confirmed to harbor the resistance locus. The physical region containing YrAev, determined from RNA-seq data, was 844.6–852.1 Mb on the chromosome arm 2Sl of the Ae. longissima (Sv genome donor species of Ae. variabilis) accession TL05 assembly v1.0. Differential gene expression analysis of post-inoculation with the Pst race has indicated two disease-resistance-related genes (annotated as mixed lineage kinase domain-like protein and nucleotide-binding leucine-rich repeat like protein, respectively) as promising candidates for YrAev. This study demonstrates the utility of the phKL gene system in alien gene localization and transfer. The resistant translocation line harboring YrAev can be exploited by wheat breeders as a novel source of resistance to stripe rust.